Niche Divergence at Intraspecific Level in the Hyrcanian Wood Frog, Rana pseudodalmatina: A Phylogenetic, Climatic, and Environmental Survey - Vaissi, Somaye; Rezaei, Sahar (Frontiers in Ecology and Evolution, 2022)
The role of ecological niche divergence in lineage speciation has recently stimulated the interest of evolutionary biologists and ecologists. Phylogenetic analysis has revealed that the Hyrcanian wood frog, Rana pseudodalmatina, has diverged into two western and eastern regional clades (WRC and ERC) within the Hyrcanian forest. The goal of this study was to investigate whether the ecological niches of WRC and ERC are conserved or diverged, as well as to figure out what variables promote niche conservatism or divergence. For this purpose, the maximum entropy model was employed to assess environmental niche modelling in geographical (G) space utilizing climatic and macro-environmental data. The niche overlap, equivalency, and similarity tests based on PCAenv analyses were used to assess niche divergence or conservatism in environmental (E) space. The findings strongly support the hypothesis that WRC and ERC have undergone substantial niche divergence and are constrained by a unique set of climatic and macro-environmental conditions. This study by ecological niche comparisons based on phylogenetic data provides new insights into the exploration of species diversification processes in the Hyrcanian forests.